Pembelian Tiket Bus Aneka Trasport Dan Po.Sejahtra Menggunakan Metode Fuzzy Inference System - Andi Irfandiari Syair Syair; Muhammad Fahril Prasetya; Fhatiah Adiba (Journal of Deep Learning, Computer Vision, and Digital Image Processing, 2023)
Aneka Transport and Po.Sejahtar is a public transportation service that has a Selayar-Makassar route, various transports and Po.Sejahtra with millions to solve problems caused by the increasing volume of vehicles going back and forth from Selayar - Makassar. This research was carried out to determine bus ticket prices using fuzzy inference system. to overcome the uncertainty and complexity in making decisions in terms of pricing based on influencing factors, such as the distance traveled, facilities, and the number of buyers.